2015
DOI: 10.1007/s12029-015-9700-9
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Urinary 5-Hydroxyindoleacetic Acid as a Metabolomics in Gastric Cancer

Abstract: Urinary excretion of 5-HIAA is significantly higher in the gastric cancer patients in comparison with that of chronic gastritis patients or normal individuals. So, this test could be regarded as a tumor marker in conjunction with other modalities in diagnosis of gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 25 publications
0
14
0
Order By: Relevance
“…Indole-containing metabolites were significantly different in fecal samples of CCM, such as 5-hydroxyindoleacetic acid (5-HIAA) and indole-2-carboxylic acid, which are nearly 100 and 300 times higher than that in the wild, respectively. Indole and its derivatives widely exist in animals, microorganisms, and plants [ 58 ], and are the main metabolites of serotonin [ 59 ]. Degg et al [ 60 ] found that excretion of indole containing metabolites, such as 5-HIAA, increased after humans ingested high serotonin-containing foods including tomatoes, bananas, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Indole-containing metabolites were significantly different in fecal samples of CCM, such as 5-hydroxyindoleacetic acid (5-HIAA) and indole-2-carboxylic acid, which are nearly 100 and 300 times higher than that in the wild, respectively. Indole and its derivatives widely exist in animals, microorganisms, and plants [ 58 ], and are the main metabolites of serotonin [ 59 ]. Degg et al [ 60 ] found that excretion of indole containing metabolites, such as 5-HIAA, increased after humans ingested high serotonin-containing foods including tomatoes, bananas, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Of note, 68.8% of patients had liver metastases. Apart from NEN, elevation of urinary 5-HIAA has been reported in several types of malignant conditions including gastric cancer [29] and breast cancer [30]. The prognostic value of 5-HIAA has been suggested for advanced disease in SBNEN [31].…”
Section: Discussionmentioning
confidence: 99%
“…Indole-containing metabolites were signi cantly different in fecal samples of CCM, such as 5hydroxyindoleacetic acid (5-HIAA) and indole-2-carboxylic acid, which are nearly 100 and 300 times higher than that in the wild, respectively. Indole and its derivatives widely exist in animals, microorganisms and plants [54], and are the main metabolites of serotonin [55]. Degg et.…”
Section: Discussionmentioning
confidence: 99%